2019
DOI: 10.1002/jcsm.12394
|View full text |Cite
|
Sign up to set email alerts
|

Protein supplementation improves lean body mass in physically active older adults: a randomized placebo‐controlled trial

Abstract: Background An inadequate protein intake may offset the muscle protein synthetic response after physical activity, reducing the possible benefits of an active lifestyle for muscle mass. We examined the effects of 12 weeks of daily protein supplementation on lean body mass, muscle strength, and physical performance in physically active older adults with a low habitual protein intake (<1.0 g/kg/day). Methods A randomized double‐blinded controlled trial was performed among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 53 publications
0
49
0
1
Order By: Relevance
“…The primary outcome measure as well as the secondary one was defined as a pooled estimate of the mean difference in change between the mean of the treatment (PS and resistance training) and the placebo (other-type supplement and resistance training) groups. If the exact variance of paired difference was not derivable, it was imputed by assuming a within-participant correlation coefficient of 0.98, 0.92, and 0.80 for lean body mass [28], muscle strength [29,30], and mobility [30,31], respectively, between the baseline and posttest measured data. If data were reported as median (range), they were re-calculated algebraically from the trial data to impute the sample mean and SD [25,32].…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome measure as well as the secondary one was defined as a pooled estimate of the mean difference in change between the mean of the treatment (PS and resistance training) and the placebo (other-type supplement and resistance training) groups. If the exact variance of paired difference was not derivable, it was imputed by assuming a within-participant correlation coefficient of 0.98, 0.92, and 0.80 for lean body mass [28], muscle strength [29,30], and mobility [30,31], respectively, between the baseline and posttest measured data. If data were reported as median (range), they were re-calculated algebraically from the trial data to impute the sample mean and SD [25,32].…”
Section: Methodsmentioning
confidence: 99%
“…The present study is a subanalysis of a larger double-blind, placebo-controlled intervention study [19], aiming to assess changes in body composition, muscle strength and physical performance at baseline and after 12 weeks of protein supplementation. Vital subjects ≥65 years old with a habitual protein intake ≤1.0 g/kg/d who were registered for the 2017 Nijmegen Four Days Marches (a annual 4 d walking event for which subjects registered to walk either 30, 40 or 50 km/d [20];) were randomly allocated to either a protein-or a placebo-supplemented group.…”
Section: Subjectsmentioning
confidence: 99%
“…Consistent with this notion, no clinical studies have shown the positive effects of leucine supplementation on lean body mass and strength, particularly in older adults. 33,34) In contrast, EAA or protein supplementation improved lean body mass in older adults, with 35) or without exercise training. 36) Moreover, at the whole-body level, the consumption of balanced EAA was more effective in inducing a greater anabolic response than that of protein in young 37) and older adults.…”
Section: All Aas Work Together To Make New Proteinsmentioning
confidence: 99%